The Evolution of Intermediary Institutions in Europe
XIII, 277 p.
Keywords: This book investigates the consecutive shifts between three types of intermediary institutions in the European context: Corporatist, Neo-corporatist and Governance institutions. It does so by combining insights from European Political Economy; European Integration and governance studies; and, socio-legal studies in the European context.